SINERGI MATA KULIAH MAGANG DENGAN KEGIATAN MICROTEACHING BAGI CALON PENDIDIK MATEMATIKA - Lutfiyah; Putra, Eric Dwi (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2021)
The existence of internship courses for students as prospective educators is expected to increase their expertise, especially inmastering the field of study and scientific foundations in educational activities. The purpose of this research is to synergize the results of internship courses and microteaching activities. This study uses a descriptive design. The results of this study in the form of evaluations obtained from internships 1 and 2, namely 82.53% very good category and 79.79% good category while the evaluations obtained in microteaching activities in evaluation 1 an average of 78.7% good category and evaluation 2 average -average 78.9% good category. The conclusion of this study is that internships 1 and 2 in the mathematics education study program averaged 81.16% in the very good category, while the evaluation results obtained in microteaching activities in the mathematics education study program averaged 78.8% in the good category. There is a relationship between internship courses and microteaching activities so that the two courses are said to be in synergy.